Analytical and experimental studies of dragging hall anchors through rock berm. (1st November 2015) - Yan, Shuwang; Guo, Bingchuan; Sun, Liqiang; Guo, Wei; Lei, Zhenming
Abstract: An analytical method is proposed in this paper to calculate the maximum embedded depth of a dragged Hall anchor when passing through rock berm and to thus define a minimum buried depth of pipelines in rock berm to prevent pipelines from being damaged by dragging anchors. The movement of a Hall anchor in rock berm is interpreted based on the equilibrium conditions for resisting and driving moments acting on the anchor. To verify the accuracy of the proposed analytical method, model tests were carried out by using three scaled Hall anchor models and dragging them through rock berm. The comparisons between the two studies show that the average value of their differences for the stable embedded depth of a Hall anchor in sand and in rock berm are only 1.7% and 2.7%, respectively. The good agreements indicate that the proposed method is accurate enough to calculate the minimum buried depth of pipeline in rock berm during pipeline design. Highlights: Ocean pipelines are likely to be exposed to the risk of damage from dragged anchors. A limit equilibrium approach is established to calculate the forces on the anchor. The rock berm can induce unbalanced moments on the dragged anchor. Model tests with different linear scale anchors are carried out.